Booklet Berbahasa Daerah Amfoang dalam Upaya Meningkatkan Pengetahuan dan Tindakan Pencegahan Stunting - Jumetan, Mili Arthanedi; Lette, Arman Rifat; Fitri, Hironima Niyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of Amfoang regional language booklets on knowledge and stunting prevention measures in fertile couples in Fatumonas Village. The method used is pre-experimental research with one group pre-test post-test design. The results of the study showed that there was a significant difference in the level of knowledge and action before and after being given Health Education using regional language booklets, the p-value obtained from the level of expertise 0.000 <0.05 and action 0.017 <0.05 which means there is a significant difference in the knowledge and actions of respondents before and after being given Amfoang language booklets. In conclusion, Amfoang language booklets effectively increase knowledge and stunting prevention measures in families. Keywords: Booklets, Fertile Couples, Stunting